Aerodynamic effects of deviating motion of flapping wings in hovering flight. (1st February 2019) - Kim, Ho-Young; Han, Jong-Seob; Han, Jae-Hung
Abstract: Nature's flyers adopt deviating motion when they fly, however, the effect of deviating motion on the aerodynamics of flapping wings is not yet clearly understood. In this study, the aerodynamic characteristics of figure-of-eight deviating motion were investigated by comparing the aerodynamic force obtained from an experiment and the quasi-steady (QS) model in wide ranges of both the pitch and deviation amplitude. A flapping-wing robotic manipulator with a one-ton water tank was used in the experiment. Digital particle image velocimetry (DPIV) was also conducted in several chordwise cross-sections and different time instants. The results showed that the increment of deviating angle dramatically reduced the aerodynamic lift in the middle of the up- or downstroke from the quasi-steady estimation. The DPIV showed a vortex loop, which inhibits lift generation, at the middle of the up- or downstroke in deviating motion. The deviating motion delayed a development of the vortices, and more stroke angle was necessary for trailing edge vortex shedding. The QS model could not properly predict the aerodynamic force of the flapping wing with significant deviation angles. The error between the experiments and the QS estimation with regard to the aerodynamic lift was as high as 35% in the middle of the up- or downstroke with a high deviation amplitude ( ), reducing the cycle-averaged value of the lift coefficient up to 30%.